Patients' Expectations for Longevity of Kidney Transplant. (March 2019) - Gruttadauria, Michelle; Dunn, Colin; Lin, Juan; Kaminetsky, Joshua R.; Applebaum, Kayla; Portal, Daniella; Mohammed, Omar; Rocca, Juan; Greenstein, Stuart
Introduction: Prior to transplantation, the transplant team is responsible for transplant education and posttransplant expectations. The majority of outcomes research focuses on 1- and 3-year graft survival, with a lack of literature focused upon whether patients have a realistic understanding of how many years deceased donor kidneys can be expected to function after transplant. Objective: To determine whether potential kidney transplant patients' expectations for how long a deceased donor kidney will function after transplantation differs from transplant surgeons, using quantitative analysis. Design: A cross-sectional survey was used with potential adult kidney transplant recipients and transplant surgeons. Patient surveys included demographics, quality-of-life questions, and questions of expectations of kidney function for deceased donor kidneys from the Kidney Donor Profile Index. The survey categorized donor organ risk as 0% to 20%, 21% to 85%, and 86% to 100%, and results were compared to responses from US Transplant Surgeons. Surgeons were contacted via e-mail using an online survey program. Results: Responses included 154 transplant surgeons and 172 patients. Surgeon and patient responses were compared using Fisher exact test, showing a significant difference in each of the donor organ categories. We found that 47% of patient respondents did not correctly interpret the Kidney Donor Profile Index continuum. Conclusion: In every organ donor category, patients had a significantly different expectation for how long a transplanted kidney will last after transplant when compared to transplant surgeons. More study is required to determine why 47% of patients did not correctly interpret the Kidney Donor Profile continuum.